Unsur Estetika Islam pada Seni Hias Istana Raja Bugis - Pangeran Paita Yunus; Soedarsono Soedarsono; SP Gustami (Al-Ulum, 2012)
Continuity in the development of art, especially Hindu art Indonesia reached a new tradition at the time of the power of the king who converted to Islam, in which the development of Islamic art in Indonesia based on the palace of the king. In this cultural arts center arts fostered and developed based on a long artistic tradition with new values ​​that Islam breath. Symbolic and aesthetic elements in the building of Islam in Indonesia, is a reflection of culture in a region of breath. Big or small the role of local culture, weighing whether or not the work of pre-Islamic art, that's what color the Islamic art forms including architecture realization. The concept of Islam, i.e. every creature possessed of art values ​​have to be connected with a wealth of beauty and greatness of Allah Swt. Thus, in Islamic art has a legal status (syar'i) are governed by certain religious teachings of Islam, both contained in the Qur'an, Hadith, and the opinions of the ulama.